2009
DOI: 10.1271/bbb.90081
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Characterization, Molecular Cloning, and Expression of a New Aminoacylase fromStreptomyces mobaraensisThat Can HydrolyzeN-(Middle/Long)-chain-fatty-acyl-L-amino Acids as Well asN-Short-chain-acyl-L-amino acids

Abstract: We report here on the purification, characterization, molecular cloning, and expression of a new aminoacylase, initially isolated from the supernatant of Streptomyces mobaraensis (Sm-AA). Purified wild-type Sm-AA was found to be a monomeric protein with a molecular mass of 55 kDa. The cloned gene of Sm-AA contained an ORF of 1,383 bp, encoding a polypeptide of 460 amino acids. A BLAST search revealed that Sm-AA belongs to the peptidase M20 family, with identities to a hypothetical protein from Streptomyces pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…This regio-specificity of the enzyme encoded by SAM23877 1734 is surprising because the enzyme Sm-AA produced by S. mobaraensis was not able to catalyze N-acetyl-L-lysine hydrolysis [12]. This result supported the hypothesis that SAM23877 1734 likely encodes a second aminoacylase, different from the product of SAM23877 1485 and specific for the hydrolysis of N-α-acetyl-L-lysine.…”
Section: Partial Purification and Research For A Sam23877 1485 And Samentioning
confidence: 70%
See 4 more Smart Citations
“…This regio-specificity of the enzyme encoded by SAM23877 1734 is surprising because the enzyme Sm-AA produced by S. mobaraensis was not able to catalyze N-acetyl-L-lysine hydrolysis [12]. This result supported the hypothesis that SAM23877 1734 likely encodes a second aminoacylase, different from the product of SAM23877 1485 and specific for the hydrolysis of N-α-acetyl-L-lysine.…”
Section: Partial Purification and Research For A Sam23877 1485 And Samentioning
confidence: 70%
“…Lipases are the most currently used enzymes to synthesize bioactive molecules, but their use involves the utilization of organic solvent as reaction medium. These enzymes are able to catalyze the acylation of amino acids or peptides with fatty acids in aqueous media [1,[8][9][10][11][12]. Studies reported the use of neoteric media such as ionic liquids, allowing the improvement of the solubility of peptides such as Lys-Ser in 1-butyl-3-methylimidazolium hexafluorophosphate ([Bmim] + [PF6] − ) in comparison with 2-methyl-2-butanol and of the reaction performances [6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations